2020
DOI: 10.26434/chemrxiv.12055395.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chloroquine and Lopinavir (COVID-19 Drug Candidates) Signal Amplification by Reversible Exchange

Abstract: <p>To overcome the recent coronavirus pneumonia (COVID-19), several drug candidates are suggested and tested for the latest clinical treatment. Chloroquine and lopinavir are showing definite effects after treatment. To understand more about those roles in molecular level and future application on NMR/MRI, hyperpolarization technique can open new opportunities in the diagnosis and biomedical researches to cope with COVID-19. SABRE-based hyperpolarization studies on those two drug candidates are carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Patients are often given empirical antiviral therapy for COVID-19 after admission, of which some can be potentially hepatotoxic. At the time of this writing, recent studies have reported that lopinavir might be potentially effective against SARS-CoV-2 [59], but lopinavir/ritonavir is mainly metabolized by cytochrome P 450 3A4 (CYP3A4) enzymes in the liver, which is likely to cause elevated serum transaminases [60]. In addition, some patients may be treated with antipyretic agents during hospitalization, of which most contain acetaminophen that can be hepatotoxic in high doses and/or combination with other drugs and even cause liver failure [61].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are often given empirical antiviral therapy for COVID-19 after admission, of which some can be potentially hepatotoxic. At the time of this writing, recent studies have reported that lopinavir might be potentially effective against SARS-CoV-2 [59], but lopinavir/ritonavir is mainly metabolized by cytochrome P 450 3A4 (CYP3A4) enzymes in the liver, which is likely to cause elevated serum transaminases [60]. In addition, some patients may be treated with antipyretic agents during hospitalization, of which most contain acetaminophen that can be hepatotoxic in high doses and/or combination with other drugs and even cause liver failure [61].…”
Section: Discussionmentioning
confidence: 99%